The fate of anti-HLA antibodies following liver transplantation - Norman, Douglas J.; Enestvedt, C. Kristian; Naugler, Willscott E.; Erhan, Rouella; Shaut, Carley A. (Frontiers in Nephrology, 2024)
IntroductionLiver transplant recipients may have pre-formed anti-HLA antibodies directed to mismatched HLA of the liver donor (donor specific antibodies, DSA) or not directed to the liver donor (non-donor specific, non-DSA). We observed the fate of these antibodies (DSA and non-DSA) at 12 months after transplant.MethodsPatients transplanted between 4/2015 and 12/2018 (N = 216) who had anti-HLA antibody measurements at both transplant and 12 months posttransplant (N = 124) and with DSAs at transplant (N = 31) were considered informative for a paired analysis of the natural history of DSA and non-DSA following liver transplantation.ResultsClass I DSAs and non-DSAs decreased between transplant and 12 months; however, Class I DSAs essentially disappeared by 12 months while Class I non-DSAs did not. Anti-HLA Class II DSAs performed differently. While there was a significant drop in values between transplant and 12 months, these antibodies mostly persisted at a low level.DiscussionOur study demonstrated a significant difference in the kinetics of DSA compared to non-DSA following liver transplantation, most profoundly for anti-HLA Class I antibodies. Class I DSAs were mostly absent at 12 months while Class II DSAs persisted, although at lower levels. The mechanisms of reduction in anti-HLA antibodies following liver transplantation are not completely understood and were not pursued as a part of this study. This detailed analysis of Class I and Class II DSAs and non-DSAs represents and important study to explore the change in antibodies at one year from liver transplantation.